Workplace violence at emergency departments, Ain Shams University Hospitals, Cairo, Egypt - Altaf O. Assil; Amna A. Salem; Omnya A. Mokhtar; Omnia H. Taha; Amany M. Ramadan; Amal H. R. Mansour; Amal A. E. Awad; Amira A. El-Hossainy; Amir A. Khattab; Alshaymaa M. Salem; Amany E. A. Dalaab; Sonya M. S. Azab (BMC, 2022)
Abstract Background The present study aimed to determine the prevalence and forms of workplace violence (WPV) at the emergency departments (EDs) of Ain Shams University Hospitals (ASUH), Cairo and identify risk factors for WPV. Methods A cross-sectional study was conducted at the EDs of ASUH comprising attending physicians and nurses using a self-administered structured questionnaire. Interviews were conducted with patients and relatives attending these departments to explore attitudes toward WPV against healthcare workers. Results The present study comprised 108 healthcare professionals working in EDs. Verbal violence was the most common type of WPV (86.1%), followed by sexual (48.1%) and physical violence (34.3%). Patient relatives were the most common perpetrator of all types of violence. A lack of facilities was the most common risk factor for violence (82.4%), followed by overcrowding (50.9%) and patient culture (47.2%). On the other hand, approximately 78% of interviewed patients and relatives agreed that the occurrence of violence at EDs was due to several triggering factors, including improper manner of communication by healthcare workers (63.2%), lack of facilities (32.4%), waiting time (22.1%), and unmet expectations (22.1%). Conclusion WPV represents a significant issue in EDs with violent behavior against healthcare workers widely accepted by attending patients.